(untitled) (Journal of Atomic and Molecular Sciences, 2016)
In present study, the dynamics of stretching-stretching and stretching-bending entanglement in H_2O are studied with considering the inherent decoherence process. It is shown that the excitation in the bending vibration can lead to the decrease of the generation rate of stretching-stretching entanglement for the non-superposed state and the degeneration of entanglement for the initial entangled states. For specific initial entangled states, the stretching-stretching entanglement can live for a long time, and the correspondence between energy transfer and entanglement is still maintained for the initial local mode states. For the stretching-bending vibrations, the stretching-bending entanglement is much lower than the stretching-stretching vibration, and the degeneration rate of stretching-bending entanglement is higher than that of the stretching-stretching entanglement. The excitation in the remaining stretching vibration can induce a higher degree of stretching-bending entanglement.